Architektura organizacyjna. Pomiędzy strukturą a przestrzenią organizacji = The organizational architecture.between the structure and the space of the organization - Dzidowski, Adam (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The relationship between the organizational structure and the work space are becoming more and more often the focus of research. It results from the fact that, since the beginnings of the scientific approach to management, these both dimensions have evolved, however not always in harmony. As far as the organizational maps (structures, hierarchies) are becoming more and more blurred, temporary and obscure (by means of network, virtual or liquid structures), the territories (buildings, offices, locations) are more often the indictor of image, identity and culture of a given organization.
Keywords: organizacja; produktywność; motywacja; relacje społeczne; tożsamość; kultura organizacyjna przedsiębiorstwa; badania